The description of post-operative nausea and vomiting in curettage while under general anesthesia - Hani, Winarni; Burhan, Asmat; Heri Wibowo, Tophan; Suandika, Made (Java Nursing Journal, 2025)
Background General anesthesia is the process of eliminating consciousness using medications. Curettage is the procedure to remove leftover conception material from the uterus. Currently, 37.5% of curettage procedures are due to blighted ovum. The curettage procedure causes discomfort, so it needs to be assisted with anesthesia. Purpose: to determine the incidence of PONV in post-curettage patients under general anesthesia. Method Descriptive research with a cross-sectional design. The respondents were 47 women who underwent curettage due to incomplete abortion, retained placenta, and blighted ovum, selected using a purposive sampling technique. The instruments used are a demographic data questionnaire and The Rhodes Index Nausea, Vomiting and Retching (RINVR). Data analysis employs frequency distribution. Result The characteristics of the respondents are dominated by young adults (89.4%) who have experienced PONV (23.4%). Other characteristics include that all of them do not smoke and use opioids. Based on the RINVR scale, the respondents predominantly experience light PONV (46.8%). Conclusion Post-curettage patients under general anesthesia predominantly experience light PONV (Postoperative Nausea and Vomiting).